2018
DOI: 10.1007/s00038-018-1190-7
|View full text |Cite
|
Sign up to set email alerts
|

It takes a village: a realist synthesis of social pediatrics program

Abstract: Objectives To better understand how social pediatric initiatives (SPIs) enact equitable, integrated, embedded approaches with high-needs children and families while facilitating proportionate distribution of health resources. Methods The realist review method incorporated the following steps: (1) identifying the review question, (2) formulating the initial theory, (3) searching for primary studies, (4) selecting and appraising study quality, (5) synthesizing relevant da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…While TARGET's program components are considerably different from a substantive point of view, two types of overarching mechanisms are triggered: confidence and mutual trust. This corresponds with previous realist‐inspired work in the field of integrated care addressing how initiatives work 68,73,74 . For instance, a realist synthesis by Tyler and colleagues identified “four consistent patterns of care that may be effective” in six unique social pediatric initiatives 74 .…”
Section: Discussionsupporting
confidence: 79%
“…While TARGET's program components are considerably different from a substantive point of view, two types of overarching mechanisms are triggered: confidence and mutual trust. This corresponds with previous realist‐inspired work in the field of integrated care addressing how initiatives work 68,73,74 . For instance, a realist synthesis by Tyler and colleagues identified “four consistent patterns of care that may be effective” in six unique social pediatric initiatives 74 .…”
Section: Discussionsupporting
confidence: 79%
“…Resilience in pre-COVID realist reviews was often associated with power-sharing and co-production, discussed in the following section. One pre-COVID realist review discussed resilience primarily at the neighborhood or meso-level, where community engagement theory was used to describe how community assets are necessary to add resilience or to buffer against stressors, such as lack of access to social determinants of health [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pre-COVID realist reviews identified power-sharing as a key mechanism at each systems level [ 30 , 36 , 37 ]. This is discussed in relation to empowerment theory [ 44 ] and community engagement theory [ 40 , 47 ]. For example, a civic engagement realist review [ 36 ] described empowerment as shared decision-making between community providers and service users.…”
Section: Resultsmentioning
confidence: 99%
“…Trust is important in both effective relationships between patient and provider, and across the health system [ 26 ]. In their realist review, Tyler et al highlight the importance of “bridgers” or “connectors” in enabling trust between families and the health system to foster integrated care [ 27 ]. Similarly, families in this study highly valued the relational aspects of integrated care; relationships with providers, and trust, were central to families’ descriptions of good care.…”
Section: Discussionmentioning
confidence: 99%